Polylactic acid-based film, food packaging film, vegetables and fruits packaging film

A polylactic acid-based film with a layered structure addresses the issues of rigidity and environmental sustainability in existing packaging films by providing excellent flexibility, transparency, and melting seal strength, while maintaining freshness for fruits and vegetables and being environmentally friendly.

JP2025037311APending Publication Date: 2025-03-18MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023144153
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing packaging films, such as those made from polypropylene and polyolefin resins, are not environmentally friendly due to their non-biodegradable nature and high rigidity, which makes them unsuitable for flexible packaging applications. Additionally, films used for fruit and vegetable packaging often suffer from hygiene issues due to direct contact with outside air through holes.

Method used

A polylactic acid-based film with a layered structure, where one layer contains a polylactic acid resin with a low D-lactic acid unit content and a biodegradable resin, and the other layer is primarily composed of a polylactic acid resin with a higher D-lactic acid unit content. This film achieves a balance of transparency, flexibility, and high melting seal strength, making it suitable for food, daily necessities, and fruit and vegetable packaging.

Benefits of technology

The polylactic acid-based film offers excellent melting seal strength, transparency, and flexibility, making it suitable for various packaging applications. It maintains freshness for fruits and vegetables by controlling respiratory effects, while also being environmentally friendly due to its biodegradable composition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037311000002
    Figure 2025037311000002
  • Figure 2025037311000003
    Figure 2025037311000003
  • Figure 2025037311000004
    Figure 2025037311000004
Patent Text Reader

Abstract

To provide a polylactic acid-based film that has sufficient transparency and softness when stiffness of polylactic acid-based resin is reduced to form a film, excellent in heat-seal strength, and can be preferably used as a film for packaging food products, daily necessaries, miscellaneous goods or the like.SOLUTION: A polylactic acid-based film has a layer (I) and a layer (II) at least on one side of front / rear of the layer (I), where the layer (I) consists of a resin composition (i) containing polylactic acid-based resin (A1) in which lactic acid unit of D-body is less than 2.0 mol% and biodegradable resin (B) other than the polylactic acid-based resin (A), and the layer (II) consists of a resin composition (ii) containing polylactic acid-based resin (A2) in which lactic acid unit of D-body is 2.0 mol% or more as a main component.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polylactic acid film having a layer made of a resin composition containing a polylactic acid resin and a biodegradable resin, and to a food packaging film and a fruit and vegetable packaging film using the same. [Background technology]

[0002] Plastics have permeated every aspect of our lives, with annual global production reaching more than 200 million tons. Plastics are widely used as packaging for foods, daily necessities, miscellaneous goods, etc. The packaging is generally used in the form of a bag, which can be obtained by a known method, for example, by melt-cutting and sealing the end face of a plastic film using a commercially available side welder (melting machine). For example, Patent Document 1 discloses a biaxially oriented polypropylene film capable of being heat-sealed as a plastic film for use in packaging materials.

[0003] On the other hand, most plastics are discarded after use, which is recognized as one of the causes of disturbance to the global environment. Therefore, in recent years, the effective use of petroleum-derived plastics, which are exhaustible resources, has been emphasized, and the use of renewable resources to replace exhaustible resources has also become important. Currently, the use of plant-derived plastics as a renewable resource in plastics is attracting the most attention. Plant-derived plastics use non-exhaustible resources and can save exhaustible resources during plastic production. Among plant-derived plastics, polylactic acid resins in particular are made from lactic acid obtained by fermenting starch, and can be mass-produced chemically and are excellent in transparency and rigidity, so they are expected to be developed as alternative materials to polystyrene, polyethylene terephthalate, etc.

[0004] For example, Patent Document 2 proposes making use of the similar properties of polylactic acid resins to polyethylene terephthalate, and using them in films and sheets for molding purposes.

[0005] Modified Atmosphere (MA) packaging is also known as a packaging bag used to keep fruits and vegetables fresh. Fruits and vegetables, such as vegetables and fruits, continue to breathe even after they are harvested. Therefore, energy is consumed by the respiration of the fruits and vegetables themselves during storage, distribution, and preservation after harvest, which causes a deterioration in freshness. Therefore, MA packaging is used to moderately suppress the respiration of fruits and vegetables and to keep them fresh.

[0006] For example, Patent Document 3 discloses a packaging material for packaging fresh produce, which is composed of a low-rigidity portion made of a synthetic resin layer and a high-rigidity portion in which a paper layer is laminated to part of the synthetic resin layer, the area of ​​the high-rigidity portion being 50 to 95%, and the low-rigidity portion having through holes. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent Publication No. 2021-169197 [Patent Document 2] Japanese Patent Application Publication No. 10-219088 [Patent Document 3] Patent Publication No. 2022-10606 Summary of the Invention [Problem to be solved by the invention]

[0008] The above-mentioned Patent Document 1 discloses a biaxial polypropylene-based film that can be heat-sealed, but the polypropylene-based film is not derived from plants or is not biodegradable, and is not environmentally friendly.

[0009] In the above-mentioned Patent Document 2, polylactic acid-based resins are used for molded products, but polylactic acid-based resins have a high elastic modulus at room temperature and become rigid when made into a film, making them difficult to use depending on the application. For example, compared to soft films using polyolefin-based resins or polyamide-based resins, polylactic acid-based resins have high film rigidity at room temperature and are difficult to use.

[0010] Furthermore, Patent Document 3 proposes using a polyolefin resin as the low-rigidity portion, providing it with through holes to improve gas (oxygen and water vapor) permeability, and using it as a film for fruits and vegetables. However, in this case, not only is the appearance of the film impaired, but there is also concern that hygiene problems may arise due to the contents coming into direct contact with the outside air.

[0011] Therefore, the present invention aims to provide a polylactic acid-based film that reduces the rigidity of polylactic acid-based resin, has sufficient transparency and softness when made into a film, has excellent melt-cutting and sealing strength, and can be suitably used as a packaging film for food, daily necessities, miscellaneous goods, etc. [Means for solving the problem]

[0012] In view of the above-mentioned circumstances, the inventors have solved the above problems and completed the present invention by creating a film having a layer made of a resin composition containing a specific polylactic acid-based resin and a biodegradable resin, and a layer made of a resin composition containing the specific polylactic acid-based resin as a main component on at least one side of the front or back of this layer.

[0013] That is, the present invention has the following aspects. [1] A polylactic acid film having a layer (I) and a layer (II) on at least one of the front and back sides of the layer (I), the layer (I) is made of a resin composition (i) containing a polylactic acid-based resin (A1) having less than 2.0 mol% of D-form lactic acid units and a biodegradable resin (B) other than the polylactic acid-based resin (A); The layer (II) is a polylactic acid film made of a resin composition (ii) containing, as a main component, a polylactic acid resin (A2) having 2.0 mol % or more of D-lactic acid units. [2] The layer (II) has a wavelength of 955 cm -1 Peak area (Ia) and 922 cm -1 The sum of the peak areas (Ic) of 922 cm -1 The polylactic acid film according to [1], having a peak area ratio (Ic / (Ia+Ic)) of 0.57 or less. [3] The polylactic acid film according to [1] or [2], wherein the layers (II) have a melt-seal strength of 15 N / 15 mm or more when melt-sealed together. [4] The polylactic acid film according to any one of [1] to [3], wherein the resin composition (ii) contains a biodegradable resin (B) other than the polylactic acid resin (A). [5] The polylactic acid film according to [4], wherein the biodegradable resin (B) contained in the resin composition (ii) is at least one selected from polybutylene succinate and polybutylene succinate adipate. [6] The polylactic acid film according to any one of [1] to [5], wherein the biodegradable resin (B) contained in the resin composition (i) is at least one selected from polybutylene succinate and polybutylene succinate adipate. [7] The polylactic acid film according to any one of [1] to [6], wherein the resin composition (i) further contains a cellulose acylate resin (C). [8] The polylactic acid film according to any one of [1] to [7], which has a haze of 60% or less as measured in accordance with JIS K7136. [9] The polylactic acid film according to any one of [1] to [8], having a tensile modulus of elasticity in both the longitudinal and transverse directions of 4.0 GPa or less, as measured in accordance with JIS K7127.

[10] The polylactic acid film according to any one of [1] to [9], which has a heat shrinkage rate of 20% or less after heating at 120°C for 5 minutes.

[11] A food packaging film using the polylactic acid film according to any one of [1] to

[10] .

[12] A film for packaging fresh produce using the food packaging film described in

[11] . Effect of the Invention

[0014] The polylactic acid film of the present invention has transparency and flexibility like polyolefin films, and also has excellent heat-cutting seal strength, so it can be suitably used as a packaging film for food, daily necessities, miscellaneous goods, etc. In particular, the polylactic acid film of the present invention has excellent heat-cutting seal strength and is suitable for bag manufacturing using a heat-cutting seal method, so it can be suitably used for packaging food, particularly for packaging fresh produce such as vegetables and fruits. [Brief description of the drawings]

[0015] [Figure 1] 1 is an ATR-IR spectrum of Example 3. [Diagram 2] 1 is an ATR-IR spectrum of Comparative Example 1. [Diagram 3] FIG. 1 is an enlarged view of the ATR-IR spectrum of Example 3 from 980 to 900 cm−1. [Figure 4] FIG. 2 is an enlarged view of the ATR-IR spectrum of Comparative Example 1 from 980 to 900 cm −1 . DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The polylactic acid film, food packaging film, and fruit and vegetable packaging film of the present invention will be described below as examples of embodiments of the present invention, although the scope of the present invention is not limited to the embodiments described below.

[0017] In this specification, the term "main component" refers to a component that accounts for 50% by mass or more when the total of the components constituting each layer is 100% by mass, preferably 60% by mass or more, more preferably 70% by mass or more, and particularly preferably 80% by mass or more. Furthermore, when it is written "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" and "preferably smaller than Y". Furthermore, "X and / or Y (X and Y are optional)" means at least one of X and Y, and means the following three cases: X only, Y only, and X and Y. Furthermore, even if the upper and lower limits of the numerical ranges in this specification are slightly outside the numerical ranges specified by the present invention, they are included in the equivalent range of the present invention as long as they have the same action and effect as those within the numerical range.

[0018] The polylactic acid film of the present invention (hereinafter also referred to as "the film") is a polylactic acid film having a layer (I) and a layer (II) on at least one of the front and back sides of layer (I), wherein the layer (I) is made of a resin composition (i) containing a polylactic acid resin (A1) having less than 2.0 mol% of D-type lactic acid units (hereinafter also referred to as "polylactic acid resin (A1)") and a biodegradable resin (B) other than the polylactic acid resin (A), and the layer (II) is made of a resin composition (ii) containing, as a main component, a polylactic acid resin (A2) having 2.0 mol% or more of D-type lactic acid units (hereinafter also referred to as "polylactic acid resin (A2)"). The resin composition (i) and the resin composition (ii) will be described below.

[0019] <Resin composition (i)> The resin composition (i) contains a polylactic acid-based resin (A1) and a biodegradable resin (B) other than the polylactic acid-based resin (A), and preferably further contains a cellulose acylate-based resin (C).

[0020] [Polylactic acid resin (A)] The polylactic acid resin (A) is a thermoplastic resin obtained by polymerizing lactic acid, and examples thereof include homopolymers of lactic acid such as poly(L-lactic acid) whose structural unit is L-lactic acid, poly(D-lactic acid) whose structural unit is D-lactic acid, poly(DL-lactic acid) whose structural unit is L-lactic acid and D-lactic acid, or mixed resins thereof, and copolymers of lactic acid and aliphatic diol and / or aliphatic dicarboxylic acid with lactic acid as the main monomer component. Here, the main monomer component refers to a monomer component that occupies 50% by mass or more and 100% by mass or less in the resin. These may be used alone or in combination of two or more kinds. Among them, homopolymer resins of lactic acid are preferred, and poly(DL-lactic acid) is particularly preferred from the viewpoint of being able to adjust the crystallinity.

[0021] Examples of the aliphatic diol include difunctional aliphatic hydroxycarboxylic acids such as glycolic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 2-hydroxy n-butyric acid, 2-hydroxy 3,3-dimethylbutyric acid, 2-hydroxy 3-methylbutyric acid, 2-methyllactic acid, and 2-hydroxycaproic acid, lactones such as caprolactone, butyrolactone, and valerolactone, ethylene glycol, 1,4-butanediol, and 1,4-cyclohexanedimethanol, etc. These may be used alone or in combination of two or more kinds.

[0022] Examples of the aliphatic dicarboxylic acid include succinic acid, adipic acid, suberic acid, sebacic acid, dodecanedioic acid, etc. These may be used alone or in combination of two or more kinds.

[0023] In addition, the polylactic acid resin (A) may contain, as a copolymerization component, an aromatic dicarboxylic acid such as terephthalic acid or an aromatic diol such as an ethylene oxide adduct of bisphenol A, within a range that does not impair the essential properties of the polylactic acid resin (A) (for example, less than 10 mass % of the polylactic acid resin (A)) in order to improve heat resistance, etc. Furthermore, as the copolymerization component, a small amount of a chain extender, such as a diisocyanate compound, an epoxy compound, or an acid anhydride, may be added for the purpose of increasing the molecular weight.

[0024] The polymerization method for the polylactic acid resin (A) can be a condensation polymerization method, a ring-opening polymerization method, or any other known polymerization method. For example, in the condensation polymerization method, L-lactic acid or D-lactic acid, or a mixture thereof, can be directly subjected to dehydration condensation polymerization to obtain a polylactic acid resin (A) having any composition. In the ring-opening polymerization method, the polylactic acid resin (A) can be obtained by using a selected catalyst and, if necessary, a polymerization regulator etc. from lactide, which is a cyclic dimer of lactic acid.

[0025] Examples of the lactide include L-lactide, which is a dimer of L-lactic acid, D-lactide, which is a dimer of D-lactic acid, and DL-lactide consisting of L-lactic acid and D-lactic acid. In the ring-opening polymerization method, these can be mixed and polymerized as necessary to obtain a polylactic acid resin (A) having any desired composition and crystallinity.

[0026] The content ratio (mol%) of L-lactic acid and D-lactic acid, which are lactic acid units constituting the polylactic acid resin (A), can be confirmed by analysis using a known method. For example, 1 mol / L methanolic sodium hydroxide solution is added to the polylactic acid resin (A) to hydrolyze it into lactic acid (monomer), which is neutralized with hydrochloric acid and then diluted with water. The content ratio (mol%) of L-lactic acid and D-lactic acid can be determined from the peak area obtained.

[0027] [Polylactic acid resin (A1)] The polylactic acid resin (A1) is a polylactic acid resin (A) in which the D-lactic acid unit (D-lactic acid content) is less than 2.0 mol %. The content of D-lactic acid units (D-lactic acid content) in the polylactic acid resin (A1) is preferably 0.1 to 1.9 mol %, more preferably 0.2 to 1.8 mol %, and particularly preferably 0.3 to 1.7 mol %. By setting the D-lactic acid unit (D-lactic acid content) within the above range, a polylactic acid film with excellent stretchability can be obtained.

[0028] The heat of crystalline fusion (ΔHm) of the polylactic acid resin (A1) is preferably 80 J / g or less, more preferably 60 J / g or less. The lower limit is usually 10 J / g, preferably 20 J / g. By setting the heat of crystalline fusion in the above range, the film tends to have low crystallinity and is less likely to become rigid.

[0029] The mass average molecular weight of the polylactic acid resin (A1) is preferably 50,000 to 400,000, and more preferably 100,000 to 250,000. When the mass average molecular weight of the polylactic acid resin (A1) is at least the lower limit of the above range, favorable practical properties tend to be obtained, and when it is at most the upper limit, the melt viscosity is not too high, and therefore good moldability tends to be obtained.

[0030] The polylactic acid resin (A1) is preferably contained as a main component of the resin composition (i). By containing the polylactic acid resin (A1) as a main component of the resin composition (i), it tends to be easy to impart the appropriate heat resistance and rigidity of the polylactic acid resin (A1) to the film. The resin composition (i) may contain the polylactic acid resin (A1) either alone or in combination of two or more kinds.

[0031] Representative examples of the polylactic acid resin (A1) preferably used in the present invention include commercially available products such as "REVODE series" manufactured by Marine Biomaterials Co., Ltd. and "NW series" manufactured by NatureWorks.

[0032] [Biodegradable resin (B)] The biodegradable resin (B) is not particularly limited as long as it is a biodegradable resin other than the polylactic acid resin (A), but is preferably a biodegradable polyester resin. By including a biodegradable polyester resin in the resin composition, the content ratio of the biodegradable resin in the entire resin composition is increased, and not only can the biodegradable function be maintained, but also the physical property of the polylactic acid resin (A), which is high in rigidity and poor in flexibility, can be easily improved.

[0033] Examples of the biodegradable polyester resin include polyester resins obtained by polycondensation of an aliphatic diol and a dicarboxylic acid, polyester resins obtained by polycondensation of an aliphatic oxycarboxylic acid, polyester resins obtained by ring-opening polymerization of a cyclic ester, etc. These may be used alone or in combination of two or more kinds.

[0034] Examples of the aliphatic diol include ethylene glycol, trimethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, etc. These may be used alone or in combination of two or more kinds.

[0035] Examples of the dicarboxylic acid include oxalic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanedioic acid, terephthalic acid, and their lower alkyl ester derivatives and acid anhydrides, etc. These may be used alone or in combination of two or more kinds.

[0036] Examples of the aliphatic oxycarboxylic acid include glycolic acid, 2-hydroxy-n-butyric acid, 3-hydroxybutyric acid, 2-hydroxycaproic acid, 5-hydroxycaproic acid, 2-hydroxy-3,3-dimethylbutyric acid, 2-hydroxy-3-methylbutyric acid, and 2-hydroxyisocaproic acid.

[0037] Examples of the cyclic ester include lactide, glycoside, and caprolactone.

[0038] The biodegradable polyester resin may contain monomer components other than these monomer components, so long as the effects of the present invention are not significantly impaired.

[0039] Among them, polyester resin obtained by polycondensation of aliphatic diol and dicarboxylic acid is preferable, at least one selected from the group consisting of polybutylene succinate resin, polybutylene succinate adipate resin, polybutylene adipate terephthalate resin, and polyethylene succinate resin is more preferable, polybutylene succinate resin and polybutylene succinate adipate resin are further preferable, and polybutylene succinate adipate resin is particularly preferable. By using these biodegradable polyester resins, a film with high transparency and low elasticity tends to be obtained.

[0040] Specific examples of the polybutylene succinate-based resin include resins synthesized by an esterification reaction and / or an ester exchange reaction between an aliphatic diol component mainly composed of 1,4-butanediol and an aliphatic dicarboxylic acid component mainly composed of a succinic acid component such as succinic acid and / or a derivative thereof, and a condensation polymerization reaction.

[0041] Specific examples of the polybutylene succinate adipate resin include resins synthesized by an esterification reaction and a condensation polymerization reaction between an aliphatic diol component mainly composed of 1,4-butanediol, an aliphatic dicarboxylic acid component mainly composed of a succinic acid component such as succinic acid and / or a derivative thereof, and adipic acid.

[0042] The density of the biodegradable resin (B) is usually 1.40 g / cm 3 Less than or equal to 1.35 g / cm 3 It is preferable that the density is 1.30 g / cm or less. 3 By setting the density of the biodegradable resin (B) in the above range, the dispersibility with the polylactic acid resin (A) tends to be improved, and the transparency tends to be improved. The lower limit of the density is usually 1.10 g / cm 3 Here, the density is a value measured in accordance with JIS K7112-A method (1999).

[0043] The melting point of the biodegradable resin (B) is not particularly limited, but the upper limit is usually 240° C. or less, and the lower limit is usually 40° C. or more. By setting the melting point of the biodegradable resin (B) within the above range, the film-forming property of the resin composition (i) tends to be good and flexibility tends to be easily imparted. Here, the melting point is the temperature indicated by the peak top of the crystal melting peak measured in accordance with JIS K7121 (2012).

[0044] The melt flow rate (MFR) of the biodegradable resin (B) is usually 1 to 10 g / 10 min, preferably 1.5 to 9 g / 10 min, and preferably 2 to 8 g / 10 min. By setting the MFR melting point of the biodegradable resin (B) within the above range, the dispersibility with the polylactic acid resin (A) is improved, and the mechanical properties of the film tend to be improved. Here, the MFR is a value measured in accordance with JIS K7210-1 (2014), and the measurement conditions are 190° C., 2.16 kg load, or 5 kg load.

[0045] The content of the biodegradable resin (B) in the resin composition (i) is usually 4 to 55 mass%, preferably 6 to 45 mass%, and particularly preferably 8 to 30 mass%. By setting the content of the biodegradable resin (B) within the above range, a film having flexibility while maintaining transparency tends to be obtained.

[0046] Specific examples of the biodegradable resin (B) preferably used in the present invention include commercially available polybutylene succinate resins such as "BioPBS FZ91PM" manufactured by Mitsubishi Chemical Corporation, and polybutylene succinate adipate resins such as "BioPBS FD92PM" manufactured by Mitsubishi Chemical Corporation.

[0047] It is preferable that the resin composition (i) contains a cellulose acylate resin (C) in addition to the polylactic acid resin (A1) and the biodegradable resin (B), since this makes it easier to obtain a film that maintains high transparency and has good flexibility.

[0048] [Cellulose acylate resin (C)] The cellulose acylate resin (C) is a resin obtained by polymerizing a cellulose derivative in which at least a part of the hydroxyl groups of cellulose is replaced by an acyl group. The acyl group that replaces the hydroxyl group is not particularly limited as long as it is a functional group in the form of removing a hydroxyl group from an oxo acid, and specific examples include a formyl group, an acetyl group, a propionyl group, a benzoyl group, and an acrylyl group. Among them, the formyl group, the acetyl group, and the propionyl group are preferable, and the acetyl group and the propionyl group are more preferable. In addition, the acyl group may be replaced by two or more kinds of acyl groups.

[0049] The degree of acyl substitution of the cellulose acylate resin (C) is usually 1.0 to 3.0, preferably 1.5 to 2.95, more preferably 1.8 to 2.93, and particularly preferably 2.0 to 2.9, from the viewpoint of improving the moldability of the resin composition and the biodegradation rate of the film.

[0050] The degree of acyl substitution of the cellulose acylate resin (C) is an index showing the degree to which the hydroxyl groups of cellulose are substituted with acyl groups. In other words, the degree of substitution is an index showing the degree of acylation of the cellulose acylate resin (C). Specifically, the degree of substitution means the intramolecular average number of hydroxyl groups substituted with acyl groups in the D-glucopyranose unit of the cellulose acylate. The degree of substitution is 1 It can be determined from the integral ratio of the signals of cellulose-derived hydrogen and acyl group-derived hydrogen by H-NMR (JMN-ECA, manufactured by JEOL RESONANCE).

[0051] The average polymerization degree of the cellulose acylate resin (C) is preferably 200 or more and 1,000 or less, more preferably 500 or more and 1,000 or less, and even more preferably 600 or more and 1,000 or less, from the viewpoint of excellent moldability of the resin composition, impact resistance of the resin molded product, or toughness of the resin molded product.

[0052] The average degree of polymerization of the cellulose acylate resin (C) is determined by the following procedure. First, the mass average molecular weight (Mw) of the cellulose acylate resin (C) is measured in polystyrene equivalent using tetrahydrofuran with a gel permeation chromatography device (GPC device: Tosoh Corporation, HLC-8320GPC, column: TSKgelα-M). Next, the polymerization degree of the cellulose acylate resin (C) can be obtained by dividing the mass average molecular weight by the molecular weight of the monomer constituting the cellulose acylate resin (C). For example, when the substituent of the cellulose acylate resin (C) is an acetyl group and the substitution degree is 2.4, the molecular weight of the monomer is 263, so that the average polymerization degree is obtained by dividing the mass average molecular weight by 263.

[0053] The density of the cellulose acylate resin (C) is usually 1.40 g / cm 3 and preferably less than 1.35 g / cm 3 and preferably less than 1.30 g / cm 3 By setting the density of the cellulose acylate resin (C) within the above range, the dispersibility with the polylactic acid resin (A1) and the biodegradable resin (B) becomes good, and the transparency tends to be improved. Here, the density is a value measured in accordance with the JIS K7112-A method (1999).

[0054] The melting point of the cellulose acylate resin (C) is usually less than 240° C., preferably less than 230° C., and more preferably less than 220° C. By setting the melting point of the cellulose acylate resin (C) within the above range, the film-forming property of the resin composition (I) tends to be good. The melting point here is the temperature indicated by the peak top of the crystal melting peak measured according to JIS K7121 (2012).

[0055] Specific examples of the cellulose acylate resin (C) include cellulose monoacetate, cellulose diacetate (DAC), cellulose triacetate (TAC), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), etc. These may be used alone or in combination of two or more.

[0056] Among these, from the viewpoint of improving the biodegradation rate of the resin molded article, cellulose acetate propionate (CAP) and cellulose acetate butyrate (CAB) are preferred, and cellulose acetate propionate (CAP) is more preferred.

[0057] The cellulose acetate propionate (CAP) is a resin obtained by polymerizing a cellulose derivative in which at least a portion of the hydroxyl groups of cellulose are substituted with acetyl groups and propionyl groups.

[0058] From the viewpoint of improving the moldability of the resin composition and the biodegradation rate of the resin molded article, the cellulose acetate propionate (CAP) has a substitution degree ratio of acetyl group to propionyl group (acetyl group / propionyl group) of usually 0.01 to 1, and preferably 0.02 to 0.1. The ratio of the degrees of substitution is 1 It can be determined from the integral ratio of the signals of hydrogen derived from the acetyl group and hydrogen derived from the propionyl group using 1 H-NMR (JEOL RESONANCE, JMN-ECA).

[0059] Specifically, the cellulose acetate butyrate (CAB) is a resin obtained by polymerizing a cellulose derivative in which at least a portion of the hydroxyl groups of cellulose are substituted with acetyl groups and butyryl groups.

[0060] From the viewpoint of improving the moldability of the resin composition and the biodegradation rate of the resin molded body, the cellulose acetate butyrate (CAB) preferably has a substitution degree ratio of acetyl groups to butyryl groups (acetyl groups / butyryl groups) of 0.05 or more and 3.5 or less, more preferably 0.5 or more and 3.0 or less. The ratio of the degrees of substitution is 1 It can be determined from the integral ratio of the signals of hydrogen derived from acetyl groups and hydrogen derived from butyryl groups using 1 H-NMR (JEOL RESONANCE, JMN-ECA).

[0061] When the resin composition (i) contains the cellulose acylate resin (C), the content is usually 1 to 40 mass%, preferably 5 to 35 mass%, and particularly preferably 10 to 25 mass%. By setting the content of the cellulose acylate resin (C) within the above range, it is easy to maintain transparency and a flexible film tends to be easily obtained.

[0062] The cellulose acylate resin (C) preferably used in the present invention is commercially available from, for example, Eastman Chemical Company.

[0063] [Other ingredients] The resin composition (i) may contain, in addition to the polylactic acid resin (A1), the biodegradable resin (B), and the cellulose acylate resin (C), additives such as the polylactic acid resin (A), other thermoplastic resins other than the polylactic acid resin (A), thermoplastic elastomers, plasticizers, inorganic particles, ultraviolet absorbers, light stabilizers, antioxidants, nucleating agents, lubricants, pigments, and dyes, within the range that does not impair the effects of the present invention. These may be used alone or in combination of two or more. For example, from the viewpoint of imparting further flexibility to the film, the resin composition (i) preferably contains a plasticizer.

[0064] (Plasticizer) The plasticizer is not particularly limited as long as it is a plasticizer used in thermoplastic resins, and examples thereof include phthalate ester compounds, aliphatic monobasic acid ester compounds, aliphatic dibasic acid ester compounds, trimellitic acid ester compounds, polyester compounds, diester compounds, phosphate ester compounds, and paraffin compounds. These may be used alone or in combination of two or more. Among them, diester compounds are preferred from the viewpoint of lowering the glass transition temperature of the polylactic acid resin (A1).

[0065] The diester compound is preferably a compound obtained by reacting a dicarboxylic acid having 2 to 6 carbon atoms with an aromatic alcohol and / or diethylene glycol monoalkyl ether, and is particularly preferably a compound obtained by reacting adipic acid with benzyl alcohol and diethylene glycol monomethyl ether. The use of the diester compound tends to lower the glass transition temperature of the polylactic acid resin (A1) and impart further flexibility to the film.

[0066] The number average molecular weight of the diester compound is not particularly limited, but generally, the smaller the molecular weight, the greater the plasticizing effect, but the lower the stability, and the greater the possibility of blocking and staining due to bleed-out on the film surface. Therefore, the number average molecular weight of the diester compound is usually 200 to 1500, preferably 300 to 1000.

[0067] The boiling point of the diester compound is usually 200° C. or higher, preferably 250° C. or higher, and more preferably 270° C. or higher. The upper limit is usually 350° C.

[0068] The content of the plasticizer in the resin composition (i) is usually 4 to 40 mass%, preferably 6 to 30 mass%, and particularly preferably 8 to 25 mass%. By setting the content of the plasticizer within the above range, a film tends to be obtained with a good balance between the plasticizing effect and the elution property.

[0069] The resin composition (i) containing these components is formed into a film by the method described below to obtain the layer (I).

[0070] The content of D-form lactic acid units in the polylactic acid resin (A) contained in the resin composition (i) is usually 0.1 to 1.9 mol %, more preferably 0.2 to 1.8 mol %, particularly preferably 0.3 to 1.7 mol %. By setting the D-lactic acid unit (D-lactic acid content) within the above range, it tends to be possible to obtain a polylactic acid film with excellent stretchability. The D-lactic acid units of the polylactic acid resin (A) contained in the resin composition (i) refer to the weighted average of the D-lactic acid units of all the polylactic acid resins (A) contained in the resin composition (i).

[0071] <Resin composition (ii)> The resin composition (ii) forming the layer (II) of the present film contains a polylactic acid resin (A2) as a main component, and preferably contains a biodegradable resin (B) other than the polylactic acid resin (A). The resin composition (ii) may contain the polylactic acid resin (A2) alone or in combination with two or more other types.

[0072] [Polylactic acid resin (A2)] The polylactic acid resin (A2) is a polylactic acid resin (A) having a D-lactic acid unit content of 2.0 mol % or more. The content of D-lactic acid units (D-lactic acid content) in the polylactic acid resin (A2) is preferably 2.1 to 60 mol %, more preferably 2.2 to 40 mol %, and particularly preferably 2.3 to 20 mol %. By setting the D-lactic acid unit (D-lactic acid content) within the above range, a polylactic acid film with low crystallinity and excellent melt-cutting sealability can be obtained.

[0073] The heat of crystalline fusion (ΔHm) of the polylactic acid resin (A2) is preferably 40 J / g or less, more preferably 20 J / g or less. The lower limit is usually 0 J / g. By setting the heat of crystalline fusion in the above range, a polylactic acid film with low crystallinity and excellent melt-cutting sealability can be obtained.

[0074] The mass average molecular weight of the polylactic acid resin (A2) is preferably 50,000 to 400,000, and more preferably 100,000 to 250,000. When the mass average molecular weight of the polylactic acid resin (A2) is at least the lower limit of the above range, it tends to be possible to obtain preferable practical properties, and when it is at most the upper limit, it tends to be possible to obtain good moldability since the melt viscosity is not too high.

[0075] Representative examples of the polylactic acid resin (A2) preferably used in the present invention include commercially available products such as "REVODE series" manufactured by Marine Biomaterials Co., Ltd. and "NW series" manufactured by NatureWorks.

[0076] [Biodegradable resin (B)] The biodegradable resin (B) may be the biodegradable resin (B) described in the resin composition (i). Among them, the biodegradable resin (B) contained in the resin composition (ii) is preferably at least one selected from polybutylene succinate-based resins and polybutylene succinate adipate-based resins, and it is particularly preferable to use a polybutylene succinate-based resin and a polybutylene succinate adipate-based resin in combination.

[0077] When the polybutylene succinate resin and the polybutylene succinate adipate resin are used in combination, the mass ratio (polybutylene succinate resin / polybutylene succinate adipate resin) is usually 1 / 99 to 99 / 1, preferably 10 / 90 to 80 / 20, more preferably 20 / 80 to 50 / 50, and particularly preferably 25 / 75 to 45 / 55. By setting the mass ratio of the polybutylene succinate resin and the polybutylene succinate adipate resin in the above range, a film having flexibility while maintaining transparency tends to be obtained.

[0078] The content of the biodegradable resin (B) in the resin composition (ii) is usually 4 to 55 mass%, preferably 6 to 45 mass%, and particularly preferably 8 to 30 mass%. By setting the content of the biodegradable resin (B) within the above range, a film having flexibility while maintaining transparency tends to be obtained.

[0079] In addition, the resin composition (ii) may contain the "other components" described in the resin composition (i) as long as the effects of the present invention are not impaired. The preferred components, contents, etc. are also as described in the resin composition (i).

[0080] The resin composition (ii) containing these components is formed into a film by the method described below to obtain the layer (II).

[0081] The content of D-form lactic acid units in the polylactic acid resin (A) contained in the resin composition (ii) is usually 2 to 60 mol %, more preferably 3 to 40 mol %, and particularly preferably 4 to 20 mol %. By setting the D-lactic acid unit (D-lactic acid content) within the above range, it tends to be possible to obtain a polylactic acid film with low crystallinity and excellent melt-cutting sealability. The D-form lactic acid units of the polylactic acid resin (A) contained in the resin composition (ii) refer to the weighted average of the D-form lactic acid units of all the polylactic acid resins (A) contained in the resin composition (ii).

[0082] The difference between the D-form lactic acid units of the polylactic acid resin (A) contained in the resin composition (ii) and the D-form lactic acid units of the polylactic acid resin (A) contained in the resin composition (i) [resin composition (ii)-resin composition (i)] is usually 2 to 30 mol %, preferably 3 to 20 mol %, and particularly preferably 4 to 15 mol %. By setting the difference in the D-lactic acid unit within the above range, it tends to be possible to obtain a polylactic acid film that is excellent in both stretchability and heat-sealability.

[0083] [Method of manufacturing the present film] The method for producing the present film is not particularly limited, and the film can be produced by a known method. For example, the resin composition (i) is melted using an extruder, extruded from a die into a film, and cooled and solidified using a cooling roll, air cooling, or water cooling to produce layer (I), and layer (II) is laminated on at least one of the front and back sides of this layer (I).

[0084] Specifically, first, the components to be contained in the resin composition (i) are mixed and kneaded, and then the components are uniformly mixed using an extruder such as a single screw extruder, a counter-rotating twin screw extruder, or a co-rotating twin screw extruder to prepare the resin composition (i). Furthermore, before mixing the components in the extruder, they may be mixed in a mixer such as a tumbler mixer, mixing roll, Banbury mixer, ribbon blender, or super mixer and then charged into the extruder, or a strand die may be connected to the tip of another kneader, and the components may be pelletized once by a method such as strand cutting or die cutting, and the resulting pellets may be charged into the extruder. Furthermore, after some of the components are pelletized once, the resulting pellets may be charged into the extruder together with the remaining components.

[0085] Thereafter, the resin composition (i) molten by the extruder is molded into a film by connecting a die such as a T-die to the tip of the extruder, and then cooled and solidified by a cooling roll to form layer (I).

[0086] The extrusion temperature is preferably about 160 to 240° C., and more preferably 170 to 220° C. Optimizing the extrusion temperature and shear conditions is effective in achieving desired values ​​of various physical and mechanical properties.

[0087] The layer (II) can also be obtained by the same method as for the layer (I).

[0088] Examples of the method for laminating the layer (I) and the layer (II) include coextrusion, extrusion lamination, thermal lamination, dry lamination, etc. For example, the present film can be produced by using a plurality of extruders to join and coextrude the resin compositions (i) and (ii) through a feed block or a multi-manifold die.

[0089] The present film is a polylactic acid film having a layer (II) on at least one of the front and back sides of a layer (I), but a plurality of layers (I) and layers (II) may be laminated.

[0090] The layer structure of the present film can be a two-layer structure of layer (I) / layer (II), or a two-type three-layer structure such as layer (I) / layer (II) / layer (I) or layer (II) / layer (I) / layer (II). Furthermore, when the present film has, for example, a layer (I) and a plurality of layers (II) having a different composition (hereinafter referred to as layers (II-1), (II-2), etc.), a three-layer structure of layer (I) / layer (II-1) / layer (II-2), a three-type five-layer structure such as layer (II-2) / layer (II-1) / layer (I) / layer (II-1) / layer (II-2), a four-layer structure of layer (I) / layer (II-1) / layer (II-2) / layer (II-3), a four-type seven-layer structure such as layer (II-3) / layer (II-2) / layer (II-1) / layer (I) / layer (II-1) / layer (II-2) / layer (II-3), and the like can be adopted.

[0091] In addition to the layer (I) and the layer (II), the present film may also have a layer (III) made of a resin composition (iii) containing another thermoplastic resin laminated thereon.

[0092] The other thermoplastic resin contained in the resin composition (iii) is not particularly limited as long as it is a thermoplastic resin used for food packaging, and examples thereof include polyolefin-based resins, polyamide-based resins, polyethylene-based resins, polypropylene-based resins, norbornene-based resins, polyester-based resins, vinyl alcohol-based resins, ethylene-vinyl alcohol-based resins, polystyrene-based resins, polyacrylic-based resins, and the like. At least one thermoplastic resin selected from these can be selected.

[0093] The resin composition (iii) may contain additives such as thermoplastic elastomers, inorganic particles, ultraviolet absorbers, light stabilizers, antioxidants, plasticizers, nucleating agents, lubricants, pigments, dyes, etc. Examples of the plasticizer include the same ones as those described above.

[0094] When the resin composition (iii) contains a plasticizer, the content thereof is preferably less than 4% by mass, particularly preferably less than 3% by mass, relative to the resin composition (iii). The lower limit is usually 0.1% by mass.

[0095] The layer (III) can be obtained by forming the layer (I) or the layer (II) in the same manner.

[0096] The present film may have one or more layers of the layer (III). In addition, the layer (III) is preferably adjacent to the layer (I).

[0097] In the present film, there are no limitations on the number of layers, the order of layers, or the type and number of layers (III), but it is preferable for the film to have at least two layers in the order of layer (I) / layer (II).

[0098] The present film may be an unstretched film or a stretched film stretched in at least one direction, but stretching in at least one direction is preferable because it imparts mechanical strength and makes it possible to produce a packaging film with excellent durability.

[0099] The method of stretching the film is not particularly limited, but the film is stretched in at least one direction by roll stretching in the film flow direction (hereinafter sometimes referred to as "machine direction" or "MD"), tenter stretching in the direction perpendicular to the film flow direction (hereinafter sometimes referred to as "transverse direction" or "TD"), etc. Alternatively, the unstretched film may be cut and stretched in at least one direction by a batch-type stretching machine.

[0100] Furthermore, when the present film is biaxially stretched in the longitudinal and transverse directions, it may be stretched in the longitudinal direction and then in the transverse direction, or it may be stretched in the transverse direction and then in the longitudinal direction. Moreover, if the film has been stretched in both the longitudinal and transverse directions, it may be stretched two or more times in the same direction. Moreover, it may be stretched in the longitudinal direction, then in the transverse direction, and then in the longitudinal direction again. Moreover, it may be stretched in the longitudinal and transverse directions simultaneously by a simultaneous biaxial stretching machine.

[0101] The stretching temperature is usually 55 to 95° C., preferably 57 to 90° C., and more preferably 60 to 85° C. If the stretching temperature is equal to or higher than the lower limit of the range, breakage of the film during stretching tends to be prevented. On the other hand, if the stretching temperature is equal to or lower than the upper limit of the range, the polylactic acid resin (A) is unlikely to crystallize during stretching, so that sufficient stretching can be performed and breakage of the film tends to be unlikely to occur.

[0102] The present film is preferably stretched at an areal stretch ratio of 20 times or less, more preferably 16 times or less, and particularly preferably 12 times or less. The lower limit is not particularly limited, but is usually 2 times or more. By setting the areal stretching ratio within the above range, it tends to be easier to impart appropriate stiffness and strength to the film.

[0103] After the stretching process, it is preferable to perform a heat treatment (heat setting) while holding the stretched film in order to suppress thermal shrinkage. Usually, in the roll method, the heat treatment is performed by contacting the stretched film with a heated roll, while in the tenter method, the heat treatment is performed while holding the film with clips. The heat treatment temperature depends on the blending ratio and type of the resin used, but is preferably in the range of 100°C to 150°C. By performing such a heat treatment, it is possible to impart better heat resistance and mechanical properties.

[0104] The thickness of the present film is usually 8 to 500 μm, preferably 10 to 450 μm, more preferably 15 to 400 μm, and particularly preferably 20 to 300 μm. If the thickness of the present film is within the above range, it tends to have excellent flexibility. When used as a food packaging film, the thickness of the present film is usually 8 to 200 μm, preferably 10 to 150 μm, and more preferably 15 to 100 μm. If the thickness of the present film is within the above range, the oxygen permeability and water vapor permeability become sufficient, and handling tends to be easy.

[0105] The thickness of the layer (I) is usually 1 to 80 μm, preferably 2 to 70 μm, more preferably 3 to 60 μm, and particularly preferably 3.5 to 50 μm. When the thickness of the layer (I) is within the above range, the flexibility of the entire film tends to be easily improved, and the strength of the package tends to be easily increased.

[0106] The ratio of the thickness of the layer (I) to the thickness of the present film is usually at least 50%, preferably at least 60%, and the upper limit is usually 95%.

[0107] The thickness of the layer (II) is usually 1 to 50 μm, preferably 1.5 to 40 μm, more preferably 2 to 30 μm, and particularly preferably 2.5 to 20 μm. When the thickness of the layer (II) is within the above range, the heat-cutting seal strength is easily improved, and the package tends to be less prone to tearing.

[0108] The ratio of the thickness of the layer (II) to the thickness of the present film is usually 40% or less, preferably 30% or less, with the lower limit usually being 5%.

[0109] The surface of the present film may have a coating layer coated with an anti-fog agent, an antistatic agent, a release agent, etc. The coating layer can be formed by extruding the film from a die into a film shape, and applying the coating layer to the film surface by a known method after cooling and solidifying with a cooling roll, air cooling, or water cooling, or after stretching the film. In addition, before forming the coating layer, the film surface can be subjected to a corona treatment by a known method.

[0110] <This film> The film may have the following physical properties:

[0111] Layer (II) of this film has a peak at 955 cm -1 Peak area (Ia) and 922 cm -1 The sum of the peak areas (Ic) of 922 cm -1 The peak area ratio (Ic / (Ia+Ic)) is preferably 0.57 or less, more preferably 0.50 or less, and even more preferably 0.45 or less. The lower limit is not particularly limited, but is 0.005 or more. The above range is preferable because it results in low crystallinity and good melt-cutting and sealing properties.

[0112] Here, the method for determining the peak area ratio is described in "Journal of the Japan Packaging Society, Vol. 20, No. 6 (2011), p. 501." Specifically, it can be determined by measuring the IR spectrum of the layer (II) of the present film using an infrared spectrophotometer under the following measurement conditions. The IR spectrum of polylactic acid resin (A) (see Figure 1) shows a peak due to crystals / amorphous crystals at 955 cm -1 and 922cm -1 are the peaks derived from the amorphous and α-crystal (crystal), respectively. In addition, to calculate the peak area, a baseline was drawn for the amorphous and α-crystal (crystal) peaks, and the area of ​​the region surrounded by the baseline and the spectrum was taken as the peak area (see Figure 3).

[0113] One method for adjusting the area ratio in the ATR-IR measurement to fall within the above range is to use a polylactic acid resin with low crystallinity. For example, a polylactic acid resin (A2) having 2.0 mol % or more of D-form lactic acid units may be used as the main component of the resin composition (II).

[0114] In the present film, the weld seal strength when the layers (II) are weld-sealed together is preferably 15 N / 15 mm or more. It is preferably 16 N / 15 mm or more, and more preferably 18 N / 15 mm or more. The upper limit is not particularly limited, but is 100 N / 15 mm or less. By being in the above range, it is preferable because the bag is less likely to break at the weld-sealed part when making a bag by weld-sealing.

[0115] Here, the melt-cutting seal is a sealing method in which a film is cut by heat and the cut portion is fused at the same time, and is a known sealing method in which two overlapping films are fused and cut by a heating wire or a melt-cutting blade with an acute tip. It is preferable to place an elastic body such as silicone rubber on the surface facing the heating wire or the melt-cutting blade.

[0116] The heat-cutting seal strength can be determined, for example, by the following measurement method. The film is cut out to 10 cm in any direction (e.g., transverse direction: TD) and 20 cm in a direction perpendicular to the arbitrary direction (e.g., longitudinal direction: MD), folded in half in the longitudinal direction (MD), and the layers (II) are melt-sealed (heater type: melt-sealing heater, heater scale: 10) so that the melt-sealing heater of a melt-sealing machine (manufactured by Fuji Impulse, tabletop sealer P300) and the arbitrary direction (e.g., transverse direction: TD) of the film are parallel to each other to obtain a melt-sealed bag. From the obtained melt-sealed bag, a strip test piece is cut out so that it is 40 mm long and 15 mm wide in a direction perpendicular to the sealing direction, and the melt-sealed part is located at the end of the strip. The strip test piece is opened 180° so that the welded seal is located in the center, both ends are clamped with a chuck, and a tensile test is performed to peel off the welded seal. The tensile tester is an IM-20 model manufactured by Intesco, and the test is performed at a tensile speed of 500 mm / min. The maximum strength at which the welded seal breaks is taken as the welded seal strength (unit: N / 15 mm).

[0117] The haze of the present film, measured according to JIS K7136 (2000), is usually 60% or less, preferably 45% or less, more preferably 30% or less, and the lower the better. By making the haze of the present film within the above range, a highly transparent polylactic acid film can be obtained, and it tends to be suitable for use as a packaging film.

[0118] The tensile modulus of elasticity of this film in both the longitudinal and transverse directions at 23°C, measured with reference to JIS K7161-1 (2014), is preferably 4.0 GPa or less, more preferably 3.8 GPa or less, and even more preferably 3.6 GPa or less. The lower limit is usually 0.5 GPa or more, preferably 0.8 GPa or more, and even more preferably 1.0 GPa or more. By setting the tensile modulus of elasticity of this film in the above range, it is possible to obtain a polylactic acid-based film having flexibility, which can be suitably used as a packaging film.

[0119] The tensile modulus is measured by cutting three test pieces having a width of 10 mm and a length of 100 mm in the vertical direction, and measuring the test piece at an ambient temperature of 23°C and a tensile speed of 5 mm / min using a tensile tester in accordance with JIS K7161-1 (2014). The tensile modulus is calculated from the average value of the three measured values.

[0120] The heat shrinkage rate of the present film after heating at 120° C. for 5 minutes is preferably 20% or less, more preferably 16% or less, and even more preferably 12% or less. The lower limit is usually 0.1% or more, preferably 0.5% or more, and even more preferably 1.0% or more. By keeping it within the above range, a film with good dimensional stability is obtained.

[0121] Here, the heat shrinkage rate is measured by taking a test piece with a 100 mm mark from the sample, heating it in an air-circulating thermostatic chamber at 120±3℃ for 5 minutes, then removing it and measuring the length between the marks on the test piece using a JIS Class 1 metal ruler. The heat shrinkage rate is calculated using the following formula. The results are shown as the average of 4 runs. Heat shrinkage rate (%) = (length before heating - length after heating) / length before heating x 100

[0122] The glass transition temperature of the present film is not particularly limited, but is usually 65° C. or lower, and preferably 62° C. or lower. The lower limit is usually 25° C. or higher. By setting the glass transition temperature of the present film within the above range, a polylactic acid film having appropriate flexibility can be obtained, and the film can be suitably used as a packaging film. The glass transition temperature is calculated from the peak temperature of the loss tangent (tan δ) measured in accordance with JIS K7244-4 (1999).

[0123] This film has an oxygen permeability of 300cc / m2, measured according to JIS K7126-2 (2006). 2 / day / atm or more is preferable. 400cc / m 2 / day / atm or more is more preferable, and 500cc / m 2 / day / atm or more is preferable. The upper limit is usually 2000cc / m2 / day / atm or less, but when used for food packaging such as fruits and vegetables, the larger the better.

[0124] This film has a water vapor permeability of 50g / m2, measured according to JIS K7129-2 (2008). 2 / day or more is preferable. 2 / day or more is more preferable, and 70 g / m 2 / day / atm or more is more preferable. The upper limit is usually 2000g / m 2 / day or less, but in the case of use for food packaging such as fruits and vegetables, the larger the better.

[0125] The film has transparency and flexibility, and therefore can be suitably used as a food packaging film. In particular, the film has oxygen permeability and water vapor permeability in the above-mentioned ranges, and therefore can be suitably used as a packaging film for packaging fruits and vegetables. Fruits and vegetables continue to breathe even after harvesting, and it is known that during storage, distribution or preservation after harvesting, the fruits and vegetables themselves consume energy through their own respiration, causing deterioration in freshness. Therefore, the film has suitable oxygen permeability and water vapor permeability, and is suitable. Therefore, it is particularly preferable that the film of the present invention has an oxygen transmission rate measured according to JIS K7126-2 (2006) and a water vapor transmission rate measured according to JIS K7129-2 (2008) both within the above ranges. EXAMPLES

[0126] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the following examples in any way.

[0127] The raw materials used in each of the examples and comparative examples are as follows. In the examples, the machine direction (MD) of the film means the flow direction in the film production process, and the transverse direction (TD) means the direction perpendicular thereto.

[0128] <Polylactic acid resin (A)> [Polylactic acid resin (A1)] A1-1: D-lactic acid ratio = 0.9 mol%, L-lactic acid ratio = 99.1 mol%, mass average molecular weight = 190,000, ΔHm = 33.5 J / g (Marine Biomaterials: REVODE190) [Polylactic acid resin (A2)] A2-1: D-lactic acid ratio = 12 mol%, L-lactic acid ratio = 88 mol%, mass average molecular weight = 200,000, ΔHm = 0 J / g (NatureWorks, NW4060D)

[0129] The heat of crystalline fusion (ΔHm) of polylactic acid resin (A) was measured according to JIS K7121 (2012) by heating a sample cut to about 10 mg from -70 to 220°C at a rate of 10°C / min using a thermal analyzer (PerkinElmer, DSC-7) and reading the heat of crystalline fusion (ΔHm) from the obtained thermogram.

[0130] <Biodegradable resin (B)> B-1: Polybutylene succinate adipate (Mitsubishi Chemical Corporation, BioPBS FD92PM): density 1.24 g / cm 3 , Melting point 84℃, MFR4g / 10min (190℃, load 2.16kg) B-2: Polybutylene succinate (Mitsubishi Chemical Corporation, BioPBS FZ91PM): density 1.26 g / cm 3 , Melting point 115℃, MFR 5g / 10min (190℃, load 2.16kg)

[0131] <Cellulose acylate resin (C)> C-1: Cellulose acetate propionate (EASTMAN CHEMICAL, CAP-482-0.5): density 1.22 g / cm 3 , acyl substitution degree = 2.5 (acetyl substitution degree = 0.1, propionyl substitution degree = 2.4), melting point 182 ° C.

[0132] [Examples 1-2, 5-6, Comparative Examples 1-3] Each raw material was prepared so as to have the ratio shown in Table 1 below. Each raw material was put into a single screw extruder, melt-kneaded and extruded at 210 ° C., and quenched with a casting roll. The discharge amount of the molten resin and the line speed were adjusted so that the average thickness was 275 μm. Next, the film was roll-stretched 2.7 times at 75 ° C. in the machine direction (MD), stretched 2.7 times at 75 ° C. in the transverse direction (TD) with a tenter, and further heat-treated at 130 ° C. in the heat treatment zone of the tenter to obtain a stretched film. The stretching area ratio was 7.3 times, the film thickness was about 40 μm, the thickness of the layer (I) was 34 μm, and the thickness of the layer (II) was 6 μm.

[0133] [Examples 3 to 4, Comparative Example 4] Each raw material was prepared so as to have the ratio shown in Table 1 below. Each raw material was put into a co-rotating twin screw extruder, melt-kneaded at 200°C, extruded, and quenched with a casting roll to produce an unstretched film with an average thickness of 275 μm. Next, the film was roll-stretched 3.0 times in the machine direction (MD) at 60°C, stretched 3.6 times in the transverse direction (TD) at 75°C with a tenter, and further heat-treated at 145°C in the heat treatment zone of the tenter to obtain a stretched film. The area stretching ratio was 11 times, the film thickness was 25 μm, the thickness of the layer (I) was 21 μm, and the thickness of the layer (II) was 4 μm.

[0134] The following evaluations were carried out using the obtained polylactic acid films of Examples 1 to 6 and Comparative Examples 1 to 4. The results are shown in Table 1 below.

[0135] [Crystalline] For the polylactic acid films of Examples 1 to 6 and Comparative Examples 1 to 4, the IR spectrum of the layer (II) was measured using an IS5 manufactured by Thermo Fisher Scientific (see FIGS. 1 and 2). The measurement conditions were: wave number 400-4000 cm -1 The number of accumulations was 64, the ATR attachment was MicromATRTM, the ATR prism was diamond (incident angle 45°C), zero filling was none, apodization was Happ-Genel, and phase correction was Mertz. 955 cm in the IR spectrum -1 and 922cm-1 The peaks at 955 cm were assigned to the amorphous and α-crystal peaks, respectively. The peak areas were calculated using OMNIC 9.3.32 (measurement / analysis software), with a baseline drawn for the amorphous and crystalline peaks, and the area enclosed by the baseline and the spectrum was taken as the peak area (see Figures 3 and 4). -1 Peak area (Ia) and 922 cm -1 The sum of the peak areas (Ic) of 922 cm -1 The peak area ratio (Ic / (Ia+Ic)) was determined and evaluated according to the following criteria. (Evaluation Criteria) ○: Peak area ratio is 0.57 or less ×: Peak area ratio exceeds 0.57 [Haze] For the polylactic acid films of Examples 1 to 6 and Comparative Examples 1 to 4, the haze was measured in accordance with JIS K7136 (2000) and evaluated according to the following criteria. (Evaluation Criteria) ○: Haze is 60% or less ×: Haze exceeds 60%

[0136] [Tensile modulus] The tensile modulus of the polylactic acid films of Examples 1 to 6 and Comparative Examples 1 to 4 was measured by cutting three test pieces with a width of 10 mm and a length of 100 mm in the machine direction, measuring the tensile modulus in MD and TD at an atmospheric temperature of 23°C and a tensile speed of 5 mm / min using a tensile tester according to JIS K7161-1 (2014), and calculating the tensile modulus from the average value of the three measured values. The obtained tensile modulus was evaluated according to the following criteria. (Evaluation Criteria) ○: Tensile modulus is 4.0 GPa or less ×: Tensile modulus exceeds 4.0 GPa

[0137] [Fusing seal strength] The polylactic acid films of Examples 1 to 6 and Comparative Examples 1 to 4 were cut out to a length of 10 cm in the horizontal direction and 20 cm in the vertical direction, folded in half in the vertical direction so that the layers (II) were facing each other, and then heat-sealed (heater type: heat-sealing heater, heater scale: 10) so that the heat-sealing heater of a heat-sealing machine (manufactured by Fuji Impulse, tabletop sealer P300) was parallel to the horizontal direction of the test piece to obtain a heat-sealed bag. From the obtained heat-sealed bag, a strip test piece was cut out so that it was 40 mm long and 15 mm wide in the direction perpendicular to the sealing direction, and the heat-sealed part was located at the end of the strip. The strip test pieces were opened 180° so that the welded seal was located in the center, both ends were clamped with a chuck, and a tensile test was performed to peel off the welded seal. The tensile tester used was an IM-20 model manufactured by Intesco, and the test was performed at a tensile speed of 500 mm / min. The maximum strength at which the welded seal broke was taken as the welded seal strength (unit: N / 15 mm), and the evaluation was performed according to the following criteria. (Evaluation Criteria) 〇: Welding seal strength is 15N / 15mm or more ×: Welding seal strength is less than 15N / 15mm

[0138] [Heat shrinkage rate] The heat shrinkage of the polylactic acid films of Examples 1 to 6 and Comparative Examples 1 to 4 was evaluated by taking test pieces with a mark at a length of 100 mm from the film, heating them in an air-circulating thermostatic chamber at 120±3°C for 5 minutes, removing them, and measuring the length between the mark lines of the test pieces using a JIS Class 1 metal ruler, according to the following criteria. (Evaluation Criteria) ◯: MD and TD heat shrinkage rate is 20% or less △: MD or TD heat shrinkage rate is 20% or less ×: Heat shrinkage in MD and TD exceeds 20%

[0139] [Table 1]

[0140] As can be seen from the results in Table 1, the polylactic acid films of Examples 1 to 6 had high melt-seal strength, good transparency, low tensile modulus, and flexibility. Furthermore, the polylactic acid films of Examples 1 to 5 had low heat shrinkage and excellent dimensional stability. On the other hand, the films of Comparative Examples 1 to 4 in which the layer (II) contained, as the main component, a polylactic acid-based resin (A) containing 0.9 mol % of D-lactic acid units, had low heat-cutting and sealing strength. [Industrial Applicability]

[0141] The film has excellent heat-seal strength, transparency and flexibility and can be suitably used as a food packaging film, and is particularly useful as a packaging film for fruits and vegetables.

Claims

1. A polylactic acid film having a layer (I) and a layer (II) on at least one of the front and back sides of the layer (I), the layer (I) is made of a resin composition (i) containing a polylactic acid-based resin (A1) having less than 2.0 mol% of D-form lactic acid units and a biodegradable resin (B) other than the polylactic acid-based resin (A); The layer (II) is a polylactic acid film comprising a resin composition (ii) containing, as a main component, a polylactic acid resin (A2) having a D-form lactic acid unit content of 2.0 mol % or more.

2. The layer (II) has a refractive index of 955 cm -1 Peak area (Ia) and 922 cm -1 922 cm for the sum of the peak areas (Ic) -1 2. The polylactic acid film according to claim 1, wherein the peak area ratio (Ic / (Ia+Ic)) is 0.57 or less.

3. 2. The polylactic acid film according to claim 1, wherein the layers (II) have a weld seal strength of 15 N / 15 mm or more when weld-sealed together.

4. The polylactic acid film according to claim 1 , wherein the resin composition (ii) contains a biodegradable resin (B) other than the polylactic acid resin (A).

5. The polylactic acid film according to claim 4, wherein the biodegradable resin (B) contained in the resin composition (ii) is at least one selected from the group consisting of polybutylene succinate and polybutylene succinate adipate.

6. The polylactic acid film according to claim 1, wherein the biodegradable resin (B) contained in the resin composition (i) is at least one selected from the group consisting of polybutylene succinate and polybutylene succinate adipate.

7. The polylactic acid film according to claim 1 , wherein the resin composition (i) further contains a cellulose acylate resin (C).

8. 2. The polylactic acid film according to claim 1, which has a haze of 60% or less as measured in accordance with JIS K7136.

9. 2. The polylactic acid film according to claim 1, which has a tensile modulus of elasticity of 4.0 GPa or less in both the longitudinal and transverse directions, as measured in accordance with JIS K7127.

10. 2. The polylactic acid film according to claim 1, which has a heat shrinkage rate of 20% or less after heating at 120° C. for 5 minutes.

11. A food packaging film using the polylactic acid film according to any one of claims 1 to 10.

12. A food packaging film according to claim 11, used for packaging fruits and vegetables.

Citation Information

Patent Citations

  • Control of degradability of polylactic acid-based resin, degradable film / sheet and formed material from the film / sheet

    JP1998219088A

  • Biaxially oriented polypropylene film and package

    JP2021169197A

  • Packaging material for keeping freshness of garden stuff, packaging body containing garden stuff, packaging method for garden stuff and manufacturing method for packaging material for keeping freshness of garden stuff

    JP2022010606A